Caracterização e criopreservação de folículos ovarianos pré-antrais de jumentas da raça nordestina - Lopes, Katia Regina Freire (2017)
The donkeys (Equus asinus) are individuals historically relevant for the occupation of inhospitable areas around the world, but they have been losing importance due to the modernization of urban centers and the creation of traction and cultivation technologies. Due to this fact, many donkey breeds are already extinct or passing through a rapid process of population decrease. Among these breeds, the Northeast donkey, an endemic breed in Brazil, is highlighted. One of the strategies for conservation is the use of biotechnologies that facilitate reproduction, such as the manipulation of oocytes enclosed in preantral follicles (MOEPF) that maximize the availability of oocytes for in vitro fertilization. The starting point for the use of this and other techniques are known reproductive physiology details of this breed as the characteristics of their gametes. The objective of this study was to estimate and to characterize the population of ovarian PFs derived from Northeast breed donkeys. Twenty females aging 5.1 ± 3.2 years and weighing 105.2 ± 18.6 kg were used. Animals were subjected to an ovariectomy procedure guided by laparoscopy for ovary collection. As the equines, donkey ovaries presented a kidney form and their parenchymal zone were extracted, taking the ovulation fossa as basis. Fragments of ovary were fixed in Carnoy, dehydrated in increasing Ethanol concentrations (70 to 99%), clarified using xylene and finally included in histological paraffin wax blocks. These blocks were serially sectioned on 7 μm slices at using a microtome. Every 120th slice was mounted on glass slides, stained with hematoxylin–eosin and read in inverted optical microscope. PFs presenting visible oocyte nuclei were measured at using an ocular micrometer and classified as primordial, primary or secondary. PFs were also classified and counted as morphologically normal, when containing an oocyte with regular shape and uniform cytoplasm, and organized layers of granulosa cells; or as degenerated, when the oocyte exhibited pycnotic nucleus and/or ooplasm shrinkage, and occasionally, granulosa cell layers became disorganized, detached from the basement membrane and/or included enlarged cells. The PF population was estimated by using the formula: (number of follicles × number of sections × thickness of sections)/(number of sections observed × range of oocyte nuclei diameter). The results allowed us to estimate a total population of 21,135.3 ± 10,646.1 PFs per animal. From this population, 91.3% PFs were classified as primordial, 8.2% PFs as primary, and 0.3% as secondary. multioocyte PFs were observed in all animals, and they were more frequently present in primordial follicles, representing 0.99% of total PFs counted. The estimated population was distributed between the right and left ovaries, at 54.6% and 45.4%, respectively. Most PFs were considered morphologically normal (90.2%) and the smallest, degenerate (9.8%). An inversely proportional relationship between age and follicular population was identified, similarly to the relation between weight and follicular population. In the second experiment, the ovarian tissue of animals from the same group was subjected to a vitrification procedure using dimethylsulfoxide (DMSO) and ethylene glycol (EG) as cryoprotectants in separate and associated. When comparing treatments, the use of DMSO 3M (81.7 ± 37.5%), EG 3M (83.7 ± 27.4%) and the combination of both DMSO 3M + EG 3M (81.8 ± 46.8%) allowed a greater percentage of follicular survival. When vitrified using the DMSO + EG combination, a higher percentage (62.5 ± 29.1%) of viable follicles was observed in relation to the other vitrification treatments (P <0.05). The TUNEL technique identified that all treatments tested showed DNA fragmentation in the follicular cells, except in the case of the DMSO 3M plus EG 3M treatment. When evaluating the presence of NORs, no significant differences were observed in the amount of NORs between the fresh and vitrified groups using DMSO 3M plus EG 3M (P >0.05). Thus, we concluded that the combination DMSO 3M plus EG was more efficient for the vitrification of ovarian tissue taken from Equus asinus, allowing adequate preservation of PAFS morphology, viability, DNA integrity and cell proliferative capacity. This work presented for the first time the estimate of ovarian preantral follicles in donkeys of the Northeastern breed and successful vitrification